Exposure of marine mussels Mytilus spp. to polystyrene microplastics: Toxicity and influence on fluoranthene bioaccumulation. (September 2016) - Paul-Pont, Ika; Lacroix, Camille; González Fernández, Carmen; Hégaret, Hélène; Lambert, Christophe; Le Goïc, Nelly; Frère, Laura; Cassone, Anne-Laure; Sussarellu, Rossana; Fabioux, Caroline; Guyomarch, Julien; Albentosa, Marina; et al.
Abstract: The effects of polystyrene microbeads (micro-PS; mix of 2 and 6 μm; final concentration: 32 μg L −1 ) alone or in combination with fluoranthene (30 μg L −1 ) on marine mussels Mytilus spp. were investigated after 7 days of exposure and 7 days of depuration under controlled laboratory conditions. Overall, fluoranthene was mostly associated to algae Chaetoceros muelleri (partition coefficient Log Kp = 4.8) used as a food source for mussels during the experiment. When micro-PS were added in the system, a fraction of FLU transferred from the algae to the microbeads as suggested by the higher partition coefficient of micro-PS (Log Kp = 6.6), which confirmed a high affinity of fluoranthene for polystyrene microparticles. However, this did not lead to a modification of fluoranthene bioaccumulation in exposed individuals, suggesting that micro-PS had a minor role in transferring fluoranthene to mussels tissues in comparison with waterborne and foodborne exposures. After depuration, a higher fluoranthene concentration was detected in mussels exposed to micro-PS and fluoranthene, as compared to mussels exposed to fluoranthene alone. This may be related to direct effect of micro-PS on detoxification mechanisms, as suggested by a down regulation of a P-glycoprotein involved in pollutant excretion, but other factors such as an impairment of the filtration activity or presence of remaining beads in the gut cannot be excluded. Micro-PS alone led to an increase in hemocyte mortality and triggered substantial modulation of cellular oxidative balance: increase in reactive oxygen species production in hemocytes and enhancement of anti-oxidant and glutathione-related enzymes in mussel tissues. Highest histopathological damages and levels of anti-oxidant markers were observed in mussels exposed to micro-PS together with fluoranthene. Overall these results suggest that under the experimental conditions of our study micro-PS led to direct toxic effects at tissue, cellular and molecular levels, and modulated fluoranthene kinetics and toxicity in marine mussels. Graphical abstract: Highlights: Micro-PS exhibited high sorption capacity for fluoranthene. Micro-PS did not modify fluoranthene bioaccumulation in marine mussels. Micro-PS exposure modulated oxidative and energetic processes in mussels. An increase in hemocyte mortality was observed in all exposed mussels. Combined exposure led to highest tissue alterations and anti-oxidant marker levels. Abstract : Exposure to polystyrene microbeads did not modify fluoranthene bioaccumulation in marine mussels but led to direct toxic effects at tissue, cellular and molecular levels under controlled laboratory conditions.